Research And Community Service Information System At LPPM Universitas MBP Medan With Unified Modeling Language (UML) - Fauzi Haris Sibolon; Sartana, Sartana; Pasaribu, Maranata; Bangkit Iyoel Siregar (Jurnal Info Sains : Informatika dan Sains, 2024)
Universitas Mandiri Bina Prestasis (UMBP) which was established in 2022 as a merger of two institutions, namely AMIK MBP with the Vocational Education program D-III Informatics Engineering and D-III Informatics Management and STIKOM with the S1 Informatics Engineering and S1 Information Systems Study Programs and the addition of 3 new study programs, namely S1 Software Engineering, S1 Accounting and S1 Entrepreneurship. Along with that, UMBP was born and developed with a commitment that was stated in the Vision of Becoming a Superior and Independent University in the field of Information Technology and Business with an Entrepreneurial Spirit at the National level in 2036 "by developing various superior programs in the fields of research, innovation, and community service, as well as the Regulation of the Minister of Research, Technology, and Higher Education (Permenristekdikti) number 44 of 2015 concerning National Standards for Higher Education, so every university must make adjustments towards meeting the standards of education, research and community service. UMBP has one institution that is tasked with research and development called the Institute for Research and Community Service (LPPM). This institution is a forum for academics to carry out research and community service. The establishment of LPPM is UMBP's strategy in an effort to realize the improvement of quality and development of technology, social and business in higher education and its implementation in the community.